The impact of aging on neutrophil functions and the contribution to periodontitis - Zi Wang; Anish Saxena; Wenbo Yan; Silvia M. Uriarte; Rafael Siqueira; Xin Li (International Journal of Oral Science)
Abstract The increasing aging population and aging-associated diseases have become a global issue for decades. People over 65 show an increased prevalence and greater severity of periodontitis, which poses threats to overall health. Studies have demonstrated a significant association between aging and the dysfunction of neutrophils, critical cells in the early stages of periodontitis, and their crosstalk with macrophages and T and B lymphocytes to establish the periodontal lesion. Neutrophils differentiate and mature in the bone marrow before entering the circulation; during an infection, they are recruited to infected tissues guided by the signal from chemokines and cytokines to eliminate invading pathogens. Neutrophils are crucial in maintaining a balanced response between host and microbes to prevent periodontal diseases in periodontal tissues. The impacts of aging on neutrophils’ chemotaxis, anti-microbial function, cell activation, and lifespan result in impaired neutrophil functions and excessive neutrophil activation, which could influence periodontitis course. We summarize the roles of neutrophils in periodontal diseases and the aging-related impacts on neutrophil functional responses. We also explore the underlying mechanisms that can contribute to periodontitis manifestation in aging. This review could help us better understand the pathogenesis of periodontitis, which could offer novel therapeutic targets for periodontitis.